Analisis Kemampuan Siswa Dalam Menyelesaikan Soal HOTS dan LOTS Materi Gerak Lurus di SMPN20 Kota Bengkulu - Esy Puspita Sari; Lastari Lastari; Reza Ayunani; Ahmad Walid (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Bima, 2021)
This study aims to determine the ability of students to solve HOTS (Higher Order Thinking Skills) and LOTS (Low Order Thinking Skills) questions at SMPN 20 Bengkulu City. This type of research is a quantitative descriptive research. Methods This research uses research methods with quantitative approaches and technical data analysis using descriptive statistics. The data collection instrument used in this study was a test of students' problem solving abilities. The research subjects were 30 students from class VIII. Based on the results of data processing research results obtained 46.66% of students who are able to solve HOTS C4 questions and 3.3% of students who are able to solve HOTS C5 questions, and 50.04% of students who are able to solve LOTS questions. From the data above, it can be concluded that the average ability of students in solving straight motion problems is still low or in the LOTS stage.